Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/10426914.2015.1070430
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Feasibility Through Performance Analysis of Green Dielectrics for Sustainable Electric Discharge Machining

Abstract: This work represents a feasibility study for the newly proposed vegetable oil based green dielectric fluids, biodielectric1 (BD1) and biodielectric2 (BD2) for Electric discharge machining (EDM). Comparative analyses for BD1, BD2 and kerosene have been studied to assess the performance in terms of material removal Rate (MRR), electrode wear rate (EWR) and relative wear ratio (RWR) for P20+ cold worked plastic injection mould steel using electrolytic grade copper electrode. Current, Gap voltage, Pulse on time (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The maximum MRR has been reported as 53.33 mm 3 /min for jatropha and 29.21 mm 3 /min for kerosene, when 18 A current, 200 µs pulse-on time, 20 µs pulse-off time, and 50 V gap voltage were maintained. Similar types of results are also noticed when WVO, palm oil, canola, and sunflower were used as dielectrics [15,61,62]. Lately, Das et al [18] investigated the performance of neem oil as a dielectric to machine Ti-6Al-4V with copper electrode, where 4-16 A current, 20-60 V gap voltage, 50-250 µs of pulse-on time, and 10-50 µs of pulse-off time were maintained.…”
Section: Impact Of These Dielectrics On the Responsesmentioning
confidence: 59%
See 2 more Smart Citations
“…The maximum MRR has been reported as 53.33 mm 3 /min for jatropha and 29.21 mm 3 /min for kerosene, when 18 A current, 200 µs pulse-on time, 20 µs pulse-off time, and 50 V gap voltage were maintained. Similar types of results are also noticed when WVO, palm oil, canola, and sunflower were used as dielectrics [15,61,62]. Lately, Das et al [18] investigated the performance of neem oil as a dielectric to machine Ti-6Al-4V with copper electrode, where 4-16 A current, 20-60 V gap voltage, 50-250 µs of pulse-on time, and 10-50 µs of pulse-off time were maintained.…”
Section: Impact Of These Dielectrics On the Responsesmentioning
confidence: 59%
“…It was observed that the dry EDM process gave better and impressive surface quality as well as small size crack on machined surface when compared to wet EDM. It was also found that the concentration of crack was more on the wall, which significantly varied with machining condition (i.e., with current, voltage, and pulse duration) Water and air [61] Steel PCD Polycrystalline diamond (PDC) possesses poor machining efficiency during EDM operation, but while machined with water as a dielectric, impressive MRR was observed. Moreover, the sharpening process of PCD with steel as an electrode gave suitable value of MRR and surface integrity along with less electrode consumption, which was better than kerosene or EDM oil [38] Water-aqueous solution of calcium chloride…”
Section: Tungsten Carbide Becumentioning
confidence: 99%
See 1 more Smart Citation
“…The energy efficiency Ee and removal efficiency Re of micro EDM were theoretically analyzed by Mohd et al [21]. Similarly, many researchers have attempted the use of new green materials and media [22][23][24] in electrical processing, which has improved the quality of the processing environment, effectively reduced energy consumption and improved the processing efficiency in actual production. Other scholars have reduced energy consumption by controlling the pulse power or improving the processing technology [25][26][27][28], which is easy to achieve in actual processing and reduces power consumption to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that liquid dielectrics exhibited better material removal efficiency, while water-oil emulsion sustained pressure for a longer time. Valaki and Rathod [16] analyzed bio-dielectrics developed from vegetable oil and kerosene while machining P20 steel, the bio-dielectrics showed better results than kerosene for MRR and EWR. Furthermore, EDM process using water oil emulsion showed that both MRR and surface roughness (SR) were influenced greatly by current.…”
Section: Introductionmentioning
confidence: 99%